A quasi-ciência da vida e o sentido de realidadeno filme e de filme na realidade: o bandido e o documentário no Brasil - Roberta Cristiane do Nascimento (2010)
This work is to analyze three Brazilian documentaries and investigate how effective the representation of the villain in Brazillian cinema. Starting from a context in which cultural artifacts observed in a national setting is not simplistic agent of wrongdoing, the paper studies the speeches and film tries to show that such representation would constitute a feedback loop between ways of thinking and making films, something that give a realistic dimension to the films and would make the film a kind of science of life.